Statistical analyses of the effects of bonding parameters and fabrication robustness on the strength of adhesive T-joints. (15th October 2019) - Sutherland, L.S.; Amado, C.; Guedes Soares, C.
Abstract: A large statistical design of experiments (DOE) based investigation has been completed into the effects of surface preparation, cleaning method and adhesive choice on the strength of marine composite T-joints. Using a new extended experimental data set guidelines for the best adhesive, surface-preparation and cleaning combinations were verified. Statistical analyses were developed that showed that fabrication methods were robust, both in terms of achieving joint fillet radii tolerances that did not compromise the joint strength, and in terms of repeatability. All parameters were found to be significant in a complex, interacting manner, and so interaction plots were invaluable to clearly represent results and allow practical engineering interpretation.